2019
DOI: 10.1016/j.artmed.2019.101713
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of knowledge representation for health care (2009–2018): Topics, trends, and challenges

Abstract: Background: In the last ten years, the international workshop on knowledge representation for health care (KR4HC) has hosted outstanding contributions of the artificial intelligence in medicine community pertaining to the formalization and representation of medical knowledge for supporting clinical care. Contributions regarding modeling languages, technologies and methodologies to produce these models, their incorporation into medical decision support systems, and practical applications in concrete medical set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…Other frequently discussed aspects of behavior are related to mental well-being and include depression [102], distress and anxiety [1,2]. In [102] Chow et al present the iCanThrive mobile app that helps women’s cancer survivors reduce symptoms of depression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other frequently discussed aspects of behavior are related to mental well-being and include depression [102], distress and anxiety [1,2]. In [102] Chow et al present the iCanThrive mobile app that helps women’s cancer survivors reduce symptoms of depression.…”
Section: Resultsmentioning
confidence: 99%
“…These systems demonstrate human-like artificial intelligence for supporting medical diagnosis, prevention, and care [1]. The knowledge that forms the basis for the AI-based support is acquired from clinical guidelines, evidence-based studies or experts, or it can be mined from electronic health records (EHRs) [2]. With the explosion in the availability of health data, collected in EHRs or acquired via wearable sensors, the scope of AI methods in medicine [3] has widened to include such data-centric methods that may be used to generate medical knowledge that drives the AI-based systems.…”
Section: Introductionmentioning
confidence: 99%
“…Findings from this study highlight the complexities of knowledge representation within digital health taxonomies and in the digital health environment. Riaño et al [ 23 ] suggested that knowledge representation in health is a complex area, particularly as the domain evolves in the face of advances in technology, such as artificial intelligence. The WHO’s DHI framework is a significant contribution to digital health and informatics research and practice reporting, via its conceptualization of the various functions of DHIs for reporting purposes [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…To achieve whole person health, health knowledge population and medical education are essential since they can help people improve their health literacy and develop healthy living habits. Through knowledge engineering, accurate and complete medical knowledge bases can be established to promote the popularization of medical knowledge among the population [90]- [93], [101]- [104], [186]. Specifically, people can easily access medical knowledge through question answering systems [187], [188], information retrieval systems [83], [85], and machine translation systems [1], [134], [189], [190], facilitating the popularization and education of medical knowledge.…”
Section: Public Healthmentioning
confidence: 99%